Underwater walinkg on non-motirized treadmill as fitness tool for both healthy and frailty subjects - Benelli, P; Colasanti, F; Cuesta-Vargas, Antonio; Ditroilo, M; Lucertini, F; Gervasi, M. (My University, 2014)
Introduction Underwater walking on non-motorized treadmill is a very popular aquatic fitness activity. Although water provides reduced gravity conditions and a non weight bearing environment, water based training has been proven to be as effective as land-based training in improving health-related fitness components (Takeshima et al., 2002), and to be suitable for both healthy (Benelli et al., 2004) and frailty/pathologic (Frangolias et al., 1997) subjects. Little data is available about the metabolic demands of underwater walking exercises on motorized treadmills, whereas, to the best of our knowledge, no studies have been carried out with non-motorized aquatic treadmills (ATM). Therefore, the aim of this study was twofold: i) evaluate oxygen consumption (V’O2 ) and heart rate (HR) responses to an increasing submaximal ATM exercise performed at 2 different immersion heights; ii) to allocate the results obtained into the latest fitness oriented exercise prescription guidelines.
Keywords: Ejercicios físicos; Underwater; Walking; Treadmill; Fitness; Healthy; Frailty